Efficacy of Rebamipide Instillation for Contact Lens Discomfort With Dry Eye. (November 2018) - Igarashi, Tsutomu; Kobayashi, Maika; Yaguchi, Chiemi; Fujimoto, Chiaki; Suzuki, Hisaharu; Takahashi, Hiroshi
Abstract : Objective: To examine the effects of rebamipide ophthalmic solution on the symptoms, signs, and cytokine concentrations in tear fluid among soft contact lens (SCL) wearers with Dry eye disease (DED). Methods: From November 2015 to June 2017, this open-label, single-arm study examined 40 eyes of 20 SCL wearers with DED who had been using daily disposable SCLs for >3 months (mean age, 30.0±8.33 years; range, 20–47 years). Signs, symptoms, and cytokine concentrations were assessed before and 4 weeks after starting 2% rebamipide ophthalmic solution 4 times/day. Dry eye disease was diagnosed according to: compromised tear dynamics (Schirmer test ⩽5 mm or tear break-up time (TBUT) ⩽5 sec); ocular surface abnormalities (positive vital staining with fluorescein or lissamine green); and presence of symptoms. Touch thresholds using a Cochet-Bonnet anesthesiometer were also determined for the cornea and conjunctivae. Symptoms were assessed using the 12-item Ocular Surface Disease Index questionnaire. Concentrations of cytokines in tear fluid were measured. Results: Significant improvements in signs were seen for TBUT, surface abnormalities, and touch thresholds. Ocular Surface Disease Index scores likewise improved significantly in all the 12 items. Of the cytokines measured, only interleukin-1β, interleukin-8, and monocyte chemotactic protein-1 were found in ≥60% of tear samples, with no significant differences in concentrations before and after rebamipide use. Conclusions: Rebamipide significantly improved all signs and symptoms in patients with DED who wore daily disposable SCLs. Rebamipide is effective for DED treatment with SCL wear.